Peran Guru Pendidikan Agama Islam dalam Menanamkan Sikap Sopan Santun Siswa di SD Negeri Inpres Tanjung Ria - Zummirrotil Aulia; Hasruddin Dute2; Izzatul Laili; Tri Kurniah Lestari; Ahmad Buchori (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to determine the description of the politeness of students at SD Negeri Inpres Tanjung Ria and to determine the role of Islamic Religious Education teachers in instilling politeness in students at the school. This study used a qualitative approach with the researcher as the key instrument. The data sources in this study consisted of primary data obtained from Islamic Religious Education teachers and students, as well as secondary data derived from supporting documents. Data collection techniques were carried out through observation, interviews, and documentation. Data validity was tested using source triangulation, technical triangulation, time triangulation, extended observation, and member check. The data analysis techniques were carried out through the stages of data collection, data reduction, data presentation (data display), and verification or drawing conclusions. The results of the study showed that: (1) students at SD Negeri Inpres Tanjung Ria generally have demonstrated good politeness. This can be seen from their daily behavior in the school environment, such as respecting teachers and all school members, respecting each other without differentiating between friends, using good language when talking to teachers and friends, listening carefully to teacher explanations, and wearing uniforms in accordance with school regulations. This attitude provides a positive response in the school environment, thus facilitating the habituation of good behavior not only at school but also in the community. (2) The role of Islamic Religious Education teachers in instilling polite attitudes in students is carried out through providing routine direction and guidance, implementing rules during the learning process, forming random discussion groups without differentiating between male and female students, with the aim of allowing students to get to know each other's characters, dare to express their opinions, and foster self-confidence in interactions.